PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SOPHIE PARIS DENGAN WORD OF MOUTH POSITIF SEBAGAI VARIABEL MODERASI (Survei pada Mahasiswi Fakultas Ekonomi Universitas Slamet Riyadi Surakarta) - Mellaty Sunny Kusumawati, Untung Sriwidodo & Sumaryanto (Universitas Slamet Riyadi, 2016)
A purchasing decision made by a consumer is undertaken on the basis of the wishes and needs of a product. Therefore the fashion companies strive to innovate to create high-quality products and having a good brand in the minds of consumers. The purpose of this research was: 1) to analyze the significance of the influence of the brand image of Sophie Paris purchases. 2) to analyze the significance of the influence of Word of Mouth (WOM) positive towards purchasing decision Sophie Paris. 3) to analyze the effect of moderation is Word of Mouth on the influence of the brand image of Sophie Paris purchases at Coed Faculty of Economics University of Slamet Riyadi. Research methods method using survey data, the type of data used was qualitative and quantitative data, the source data used the primary data and the data of second. The population in this research is student courses accounting and Management Faculty of Economics University of Surakarta Slamet Riyadi on force 2012-2015 as much as 540 people. As for the number of samples used in the study was as many as 70 students, with sampling techniques used in this research is to Accidental sampling method. Methods of data collection were used: questionnaires, observation and documentation. Technique of data analysis used the test of validity, reliability test, test the assumption of Linear regression analysis, classic Double, t test, F test, the coefficient of determination and the absolute difference test. The research results obtained conclusions: 1) Testing the significance of the influence of brand image against a decision of purchase Sophie Paris acquired p-value of 0,05 then Ho 0.000 < rejected means there is a significant influence on brand image against a decision of purchase Sophie Paris 2) Testing the significance of positive Word of Mouth influence against the purchasing decisions of Sophie Paris acquired p-value of 0,007 < 0,05 then Ho denied means there is a significant influence of positive Word of Mouth against the purchasing decisions of Sophie Paris 3) acquired the absolute difference in the test Results of the p-value of 0,163 > 0,05, thus it can be concluded that the variable is positive Word of Mouth does not moderate the influence of variable brand image against Sophie's purchasing decisions.Keywords: brand image, Word of Mouth positive, purchasing decisions